Applications of chemometrics to the analysis and interpretation of forensic physical evidence - Sauzier, Georgina Yasmin (Curtin University, 2016)
Forensic investigations often rely upon items of physical evidence. However, current interpretation protocols for such evidence are subjective, leading to potential bias in forensic examinations. Chemometric techniques may be used to develop more objective methods for assessing evidential significance, as well as establishing statistically validated evidential procedures. This dissertation describes the application of chemometrics to various aspects of physical evidence examination, with a specific focus on textile fibres, pen inks and explosive residues.